Impact of the use of the ultra-portable digital x-ray with CAD4TB for active case finding for tuberculosis in Nigeria - Alege, Abiola; Useni, Sani; Ihesie, Austin; Eneogu, Rupert; Agbaje, Aderonke; Odume, Bethrand; Nongo, Debby; Chukwu, Eze; Ogbudebe, Chidubem; Oyelaran, Omosalewa; Anyomi, Chris; Akingbesote, Samuel; et al. (Frontiers in Digital Health, 2025)
BackgroundThe ultra-portable digital x-ray (UPDX) with computer-aided detection (CAD) is a new technology aimed at bringing tuberculosis (TB) screening innovations to hard-to-reach communities and strengthening the active case-finding (ACF) interventions for TB. As TB control measures remain critical globally and in Nigeria, the country acquired and rolled out 10 UPDX with computer-aided detection (CAD4TB) software in eight states. This study seeks to evaluate the efficiency and impact of the UPDX with CAD4TB for TB case finding in Nigeria.MethodsA retrospective cross-sectional study involving the review of records of individuals 4 years and above who had presented for TB screening during ACF activities conducted using the UPDX with CAD4TB between January 2022 and September 2022.ResultsA total of 94,694 subjects aged 4 years and above were screened for TB with an average presumptive TB proportion of 10.84 ± 5.42% and 10% confirmed TB (r = 0.684, p = 0.03 and r(df) = 0.867, p = 0.001). The number needed to screen (NNS) to find one TB case in Northern Nigeria was 39 as against 37 for the South (χ2 = 108, p = 0.25), with correlations (r = −0.422, p = 0.17 and r(df) = −0.575, p = 0.05). Similarly, a comparison of the number needed to test (NNT) to find one TB case in Northern and Southern Nigeria gave a North total of four against a South total of five (χ2 = 60, p = 0.3), with correlations (r = −0.033, p = 0.92 and r(df) = −0.212, p = 0.51). Among the TB cases confirmed, 3.4% were asymptomatic with cough and fever absent in 18.2% and 83.2%, respectively. The average time to diagnosis (TTD) was 2.0 ± 1.04 days while the average time to treatment (TTT) was 4.2 ± 1.14 days, with 50.6% receiving same-day diagnosis and 34.5% receiving same-day treatment. The cumulative risks of radiation exposure on healthcare workers using UPDX with CAD4TB and adhering to personal protective practices were found to be low.ConclusionWe documented the usefulness of UPDX with CAD showing a high TB prevalence and test positivity rate, with significant burden of subclinical TB. This has highlighted the need to scale up its use for ACF for TB and select CAD thresholds for both children and adults.